Design and Development Approach of Smart Glove for Post Stroke Rehabilitation - Fariha Mohd Nawi, Nurhazlinda; Huong Kah Ching, Audrey; Ibrahim, Nabilah; Nur Hafsha Wan Kairuddin, Wan; Anida Jumadi, Nur; Mohd Aizat Raja Izaham, Raja; Hong-Seng, Gan; Mahani Hafizah Wan Mahmud, Wan (International Journal of Engineering and Technology, 2018)
Stroke accounts for high rates of mortality and disability. It levies great economic burden on the affected subjects, their family and the society at large. Motor impairments after stroke mainly manifest themselves as hemiplegia or hemiparesis in the upper and lower limbs. Motor recovery is highly variable but can be enhanced through motor rehabilitation with sufficient movement repetition and intensity. Some previous studies regarding home-based rehabilitation process have shown improvement in promoting human movement recovery. However, the existing rehabilitation devices are expensive and need to be supervised by physical therapist, which are complicated to be use at home. Cost effective assistive devices that can augment therapy by increasing movement repetition both at home and in the clinic may facilitate recovery. This current work aims to develop a device that can enhance motor recovery by providing feedback to both the therapist and the patient on the number of hand movements (wrist and finger extensions) performed during therapy. Further work will reveal whether this feedback can enhance recovery of hand function in neurologically impaired patients. In conclusion, this project may pave a new way in the development of new arm rehabilitation monitoring devices which can benefit human lives.Â Â